Simple Lumen Method Calculations for Louver Luminaire - Chaiyakul, Yingsawad (Journal of Architectural/Planning Research and Studies (JARS), 2020)
In practice, a chance for an architect to involve in lighting scheme for building is high. Often, the architect participation in lighting system is to distribute luminaires into space. In this study, an initial online survey was set to question various experienced architects about their involvement in lighting appraisal. The questionnaire findings suggested that the most used techniques are rules of thumb, previous experience and other comprehended techniques. In artificial lighting, a method of determining the luminaire is using a mathematical model for instance the Lumen Method. Although, the method requires not many component inputs, it is necessary to obtain data from the manufacture. Information about the room maintenance are also essential. Obtaining information in the Lumen Method is obstacle to architect’s preference. This paper goal is to examine the Lumen Method to introduce adjustments in the calculating model. The study focused on room installed with tube lamps housed in the louver luminaire. The obtained models were then used to calculate the averaged illuminance, which were then compared with the measured valves from the survey. Finally, the calculation model was again examined to derive a simpler equation. The calculation examples were shown where they can be guidance to architects. To validate the derived equation, the calculated illuminance values from the derived model were compared and contrasted with various computed illuminance values by DIALux 4.13. The results show that the simple lumen method calculations for louver luminaire are reasonable to be adopted.